The effect of consumer lockdown on the relationship between environmental beliefs and pro-environmental behaviors (2023)
This study investigates the disruptive effect of the COVID-19 lockdown on the relationship between environmental beliefs and pro-environmental behaviors. We used a survey conducted in the four major cities of Colombia before COVID-19 arrived in December 2019 and then repeated it in October 2020, after most of the major restrictions on mobility and economic activity had been lifted. The survey captured ecocentric and anthropocentric beliefs using the New Ecological Paradigm (NEP) and Pro Environmental Behaviors (PEBS) using 18 questions about energy and water savings, recycling, and sustainable purchasing.